Access to skilled labor, institutions and firm performance in developing countries. Issue 2 (7th May 2019) - Mertzanis, Charilaos; Said, Mona
Abstract : Purpose: The purpose of this paper is to examine the role of access to skilled labor in explaining firms' sales growth subject to the controlling influence of a wide range of firm-specific characteristics and country-level economic and non-economic factors. Design/methodology/approach: The analysis uses a consistent and large firm-level data set from the World Bank's Enterprise Surveys that includes 138 developing countries. An instrumental variables model with a GMM estimator is used for estimating the impact of access to skilled labor on firm performance. In order to obtain more robust estimators, the analysis introduces country-level controls reflecting the influence of economic and institutional factors, such as economic and financial development, institutional governance, education and technological progress. Findings: The results document a significant and positive association between access to skilled labor and firm performance in the developing world. The explanatory power of access to skilled labor remains broadly robust after controlling for a wide range of firm-specific characteristics: sectoral and geographical influences matter. The results also show that the association between labor skill constraints and firm performance is mitigated by country-level factors but in diverse ways. Development, institutions, education and technological progress exert various mitigating effects on firm-level behavior regarding access to skilled labor. Originality/value: The paper's novel contribution is threefold: first, it uses joint firm, sector and country-level information to analyze the role of access to skilled labor on firm performance; second, it uses consistently produced information at the firm level from 138 developing countries; and, third, it considers the controlling impact of a wide range of country-level factors that reflect a country's overall development, institutions and evolution.